Gold nanoparticles produced by laser ablation in distilled water assisted by electric field. Issue 11 (2nd December 2022) - Cutroneo, Mariapompea; Havranek, Vlamidir; Vacik, Jiri; Torrisi, Lorenzo; Silipigni, Letteria; Malinsky, Petr; Mackova, Anna
Abstract : The synthesis of metallic nanoparticles has raised a growing interest in recent years, owing to the potential applications as biosensors or contrast medium for X-ray diagnostic imaging. The gold nanoparticles have been created by laser ablation in distilled water assisted by an electric field. The different sizes and shapes of generated nanoparticles have been morphologically characterized by Scanning Electron and Atomic Force microscopies. The optical properties of the suspensions containing nanoparticles have been studied with the UV–VIS spectroscopy. The nanoparticle dispersion, as well as their composition and concentration, have been analyzed by Energy Dispersive X-ray analysis.